Exploring Adolescent Moral Reasoning in Middle School: Relational Systemic Paradigm Study - Palasara Brahmani Laras; Nur Hidayah; M. Ramli (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study aimed to describe the level of moral reasoning of adolescents in Yogyakarta with different levels of education as a measuring tool for comparison of results and examine them using a systemic-relational paradigm. The research design was a quantitative descriptive survey of adolescents in three secondary schools using purposive sampling. There were 94 junior high school, 93 high school, and 90 vocational high school students. The instrument used in this study was Rest's Defining Issues Test (DIT2) to measure adolescent moral reasoning. The results showed that students' ethical reasoning at different levels of education was mainly at level II (conventional), with stage 4, which was oriented towards legal, social, and religious order, or law and order. The data were then analysed and reviewed using a relational systemic paradigm approach to determine the factors that influence the moral reasoning of adolescents at school. Students' moral reasoning is influenced by their interactions with their environment, family, peers, educational institutions, personal experiences, culture, religion, and perceptions of justice and truth. This paradigm recognises that moral reasoning is not only the result of individual processes but is also influenced by broader environmental factors. Therefore, moral education must focus on students' social and ecological contexts to facilitate the development of better moral reasoning.